2008
DOI: 10.1021/jp0774995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase Structure of MnO2 Nanorod Catalyst on the Activity for CO Oxidation

Abstract: The R-, β-, γ-, and δ-MnO 2 nanorods were synthesized by the hydrothermal method. Their catalytic properties for CO oxidation were evaluated, and the effects of phase structures on the activities of the MnO 2 nanorods were investigated. The activities of the catalysts decreased in the order of R-≈ δ-> γ-> β-MnO 2 . The mechanism of CO oxidation over the MnO 2 nanorods was suggested as follows. The adsorbed CO was oxidized by the lattice oxygen, and the MnO 2 nanorods were partly reduced to Mn 2 O 3 and Mn 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
388
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 596 publications
(411 citation statements)
references
References 49 publications
21
388
0
2
Order By: Relevance
“…The TPR profile for samples doped with Mn showed two peaks (Table 2). According to what was seen in previous works (Hoflund et al 1995;Ferrandon et al 1999;Stobbe et al 1999;Arena et al 2001;PalDey et al 2005;Xu et al 2006;Ramesh et al 2008;Liang et al 2008;Wang et al 2008Wang et al , 2009Carabineiro et al 2010a), the reduction of MnO 2 to Mn 3 O 4 generates a peak at *350°C, whereas reduction of Mn 3 O 4 to MnO produces a peak at *450°C, sometimes with some overlapping between the two. This matches well with the results obtained for the Mn/alumina samples.…”
Section: Temperature Programmed Reductionsupporting
confidence: 57%
“…The TPR profile for samples doped with Mn showed two peaks (Table 2). According to what was seen in previous works (Hoflund et al 1995;Ferrandon et al 1999;Stobbe et al 1999;Arena et al 2001;PalDey et al 2005;Xu et al 2006;Ramesh et al 2008;Liang et al 2008;Wang et al 2008Wang et al , 2009Carabineiro et al 2010a), the reduction of MnO 2 to Mn 3 O 4 generates a peak at *350°C, whereas reduction of Mn 3 O 4 to MnO produces a peak at *450°C, sometimes with some overlapping between the two. This matches well with the results obtained for the Mn/alumina samples.…”
Section: Temperature Programmed Reductionsupporting
confidence: 57%
“…No XPS peaks of other Mn species were observed. This suggests that manganese species were present predominantly as MnO 2 in all the samples (Liang et al, 2008). In addition, the results above indicated that the use of different precursors and the 0.5% SO 4 2− doping did not change the binding energy of Mn 2p.…”
Section: Xps Resultsmentioning
confidence: 74%
“…The reduction peaks of δ-MnO 2 were similar to that of α-MnO 2 at 299 and 324°C, respectively. According to the literature, the lower temperature peak might be associated with the reduction of MnO 2 to Mn 3 O 4 , whereas the higher reduction peak should be attributed to the reduction of Mn 3 O 4 to MnO (Liang et al, 2008). The TPR profiles of β-MnO 2 and γ-MnO 2 were different from that of the α-and δ-MnO 2 .…”
Section: Catalytic Oxidation For Formaldehydementioning
confidence: 91%